Nanoparticles-based Chemo-Phototherapy Synergistic Effects for Breast Cancer Treatment : A Systematic Review - Muhammad Redza, Mohd Radzi; Lim, Chun Kim; Nadiah, Sulaiman; Khairunadwa, Jemon (Biointerface Research, 2022)
Despite the promising outcomes, conventional therapies for breast cancer treatment suffer from apparent limitations, including systemic toxicity, adverse reactions, and tumor recurrence. In light of that, therapy that combines chemo-phototherapy with nanoparticles is of immense value as it provides an alternative that hope exerts better outcomes. This review systematically assesses publications between 2010 and 2022, focusing on the application of nanoparticles in chemo-phototherapy for breast cancer. A detailed search was conducted in Scopus, PubMed, and WoS, and relevant studies within the 11 years were selected. Final 18 out of 40 initial papers were selected, including studies on in vivo analysis. Detailed information on chemo-phototherapy effects, drug cargo design, the toxicity of nanomaterials, and immunomodulatory effects were extracted and discussed. This review demonstrates the promising anticancer activity of combined synergistic effects for breast cancer management.